IgG4-Related Disease Presenting as Isolated Scleritis. (9th January 2017) - Berkowitz, Eran; Arnon, Ella; Yaakobi, Alona; Cohen, Yuval; Tiosano, Beatrice
Abstract : A rare case of IgG4-related disease (IgG4-RD) manifesting as nodular scleritis is presented in a 20-year-old female. Patient complained of left eye pain and redness for one week. Ocular examination together with ancillary testing led to the diagnosis of nodular scleritis. Since the patient did not show apparent improvement after one week of systemic steroidal treatment, she underwent a biopsy of the affected area revealing histopathological characteristics of IgG4-RD. Long-term treatment with corticosteroids and a steroid-sparing agent (methotrexate) led to significant improvement in signs and symptoms. This case highlights the significance of IgG4-RD in the differential diagnosis of scleritis and raises the question as to whether various organs affected by IgG4-RD may have different underlying pathophysiological mechanisms in which pathogenic T cells play a role.